CO2 Sequestration and Enhanced Oil Recovery at Depleted Oil/Gas Reservoirs. (July 2017) - Dai, Zhenxue; Viswanathan, Hari; Xiao, Ting; Middleton, Richard; Pan, Feng; Ampomah, William; Yang, Changbing; Zhou, Youqin; Jia, Wei; Lee, Si-Yong; Cather, Martha; Balch, Robert; et al.
Abstract: This paper presents a quantitative evaluation of the operational and technical risks of an active CO2 -EOR project. A set of risk factor metrics is defined to post-process the Monte Carlo (MC) simulations for statistical analysis. The risk factors are expressed as measurable quantities that can be used to gain insight into project risk (e.g. environmental and economic risks) without the need to generate a rigorous consequence structure, which include (a) CO2 injection rate, (b) net CO2 injection rate, (c) cumulative CO2 storage, (d) cumulative water injection, (e) oil production rate, (f) cumulative oil production, (g) cumulative CH4 production, and (h) CO2 breakthrough time. The Morrow reservoir at the Farnsworth Unit (FWU) site, Texas, is used as an example for studying the multi-scale statistical approach for CO2 accounting and risk analysis. A set of geostatistical-based MC simulations of CO2 -oil/gas-water flow and transport in the Morrow formation are conducted for evaluating the risk metrics. A response-surface-based economic model has been derived to calculate the CO2 -EOR profitability for the FWU site with a current oil price, which suggests that approximately 31% of the 1000 realizations can be profitable. If government carbon-tax credits are available, or the oil price goes up or CO2 capture and operating expenses reduce, more realizations would be profitable.